The application of a general mathematical morphological particle as a novel indicator for the performance degradation assessment of a bearing. (1st January 2017) - Li, Hongru; Wang, Yukui; Wang, Bing; Sun, Jian; Li, Yaolong
Abstract: Bearing performance degradation assessment is a key step of condition-based maintenance. In this paper, a novel indicator of bearing performance degradation assessment is presented based on the mathematical morphology (MM) theory for higher efficiency. Because the traditional mathematical morphology particle (MMP) is unable to exactly describe the bearing's performance degradation, we extended its definition to the general space to address the limited ability of the former definition. On the basis of the innovative definition, we used the morphology erosion operation instead of the morphology open operation to calculate the general mathematical morphology particle (GMMP) of the bearing's whole life data. The analysis of the simulation and practical application demonstrated that the proposed index is feasible and effective to indicate the performance degradation of the bearing. Highlights: A novel performance degradation indicator of a bearing was studied based on MM theory. The mathematical morphology particle was insufficient to indicate the bearing's degradation. The General Mathematical Morphological Particle method is defined. The general mathematical morphology particle can reflect a bearing's degradation process.